Collaboration of the mathematicians of the Baltic and Nordic agricultural universities - Kaminskienė, Janina; Raškinienė , Danutė (Lietuvos matematikos rinkinys, 2004)
In this paper we present the motives and the ways of cooperation between the Baltic and Nordic agricultural universities.
Keywords: agrometrics; knowledge of mathematics; testing